(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
The paper considers a group of channels in a cell of mobile users. Estimating serving properties in a group is not simply because a high complexity of the traffic process does not allow the implementation of Erlang and other known calculation procedures. The cell characteristics are a limited number of traffic sources, external and intra-cell traffic, and prioritized serving of handover traffic (with channel reservation). Universal simulation program which allows properties estimation (for example, traffic loss) of such a model with several input parameters has been developed. The main paper contributions are summarized as 1. simplifying and, in some cases, even enabling analysis of complex traffic scenarios in mobile telephony systems; 2. it is allowed to follow these systems’ behaviour when input parameters (number of reserved traffic channels only for handover calls, part of intra-cell traffic in total traffic, number of mobile users in the cell) one by one or at the same time gradually approach their limiting values. The simulation model verification is performed using the model where one or two factors are missing among the total number of factors for which calculation procedures exist. The description of the simulation program and numerical examples are presented in the paper.